Bone betrayal: avascular necrosis in psoriatic arthritis - Vijay, Chagalakondu Guru; Prasanna, Parimi Vijaya; Chakravarthy, Revanth; Mogiligari, Sreeja (International Journal of Research in Dermatology, 2025)
Psoriatic arthritis is a multifaceted inflammatory condition with varied musculoskeletal manifestations. Although hip joint involvement remains uncommon, but may lead to severe sequelae such as avascular necrosis (AVN), especially in the presence of steroid exposure. We report the case study of a young male with history of chronic plaque psoriasis who presented with pain of lower back and right hip. There were no records of any corticosteroid exposure, trauma, alcohol consumption or any metabolic disorders. On examination, the patient was found to have enthesitis and nail changes, suggesting possibility of psoriatic arthritis. Magnetic resonance imaging revealed grade 2 AVN of the right femoral head without sacroiliitis. This case study highlights the possible occurrence of AVN in patient with psoriatic arthritis. This could be attributable to the mechanisms causing systemic inflammation and disruption of the vascular integrity. It emphasizes the need to screen for atypical manifestations in PsA so as to enable timely management.